Determination of the degree of helminth infestation of the ecaudate amphibians (the Anura: Ranidae, Bufonidae) depending on the biotic factors in conditions of the Republic of Moldova - Elena Gherasim; Dumitru Erhan; Viorica Coadă; Ana Țîganaș (Acta et Commentationes: Ştiinţe Exacte şi ale Naturii)
In this study is made an ecological analysis of the species composition, structure of the helminth community and the invasion degree of Ranidae and Bufonidae families in different habitats in Moldova. As a result, it has been established the presence of 17 helminths species. It was found that the diversity of helminth fauna of the studied amphibians is structured depending on the host species, biotop, biotic factors, gender and depending of the host onthogenesis. Thus, the greatest diversity of helminthes in amphibians in the family Ranidae was established in Rana ridibunda and Rana lessonae with 17 species, and for the species from the Bufonidae family, no different values were established, so each host species being infested with 3 species of helminthes.